2010
DOI: 10.1016/j.arr.2010.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of mitochondrial calcium as a pharmacological target for Alzheimer's disease

Abstract: Perturbed neuronal calcium homeostasis is a prominent feature in Alzheimer's disease (AD). Mitochondria accumulate calcium ions (Ca(2+)) for cellular bioenergetic metabolism and suppression of mitochondrial motility within the cell. Excessive Ca(2+) uptake into mitochondria often leads to mitochondrial membrane permeabilization and induction of apoptosis. Ca(2+) is an interesting second messenger which can initiate both cellular life and death pathways in mitochondria. This review critically discusses the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 115 publications
(131 reference statements)
0
29
0
1
Order By: Relevance
“…Ab is also associated with modulation of mitochondrial Ca 2? levels leading to alterations in organelle physiology and enhancing self fragmentation [105]. Being metabolically highly active, aberrant mitochondrial function in photoreceptors and RPE can have a significant impact in AMD.…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Ab is also associated with modulation of mitochondrial Ca 2? levels leading to alterations in organelle physiology and enhancing self fragmentation [105]. Being metabolically highly active, aberrant mitochondrial function in photoreceptors and RPE can have a significant impact in AMD.…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Impairment of fission and fusion has been considered to be one of the pathophysiological indexes in AD (Santos et al 2010). There are some suggestions that Aβ peptides will modulate the cytosolic Ca 2+ level in mitochondria that may alter the mitochondrial morphology and physiology (Hung et al 2010). For example, elevated cytosolic Ca 2+ level may enhance the fragmentation of mitochondria and hence lead to the perturbation of fission and fusion balance which may eventually cause mitochondrial dysfunction (Saotome et al 2008).…”
Section: Ad-related Retinal Degeneration Advancing Both the Retinal Dmentioning
confidence: 99%
“…Three-dimensional structure analysis revealed that Aβ oligomers could form a channel in bilayer, and another study showed the channel display a strong selective affinity for Calcium (Figure 2) [115,116]. Therefore, the “modulation of mitochondrial calcium as a pharmacological target for Alzheimer’s disease” has been recently proposed [117]. …”
Section: The Potential Of the Mcu As A Target For Neurodegenerativmentioning
confidence: 99%